K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(A=-9x^{7-n}y^{6-n}+\dfrac{10}{3}x^{5-n}y^{4-n}+2x^{3-n}y^{2-n}\)

Để đây là phép chia hết thì 7-n>=0; 6-n>=0; 5-n>=0; 4-n>=0; 3-n>=0; 2-n>=0

=>2-n>=0

=>n<=2

\(=-x^2y^3\cdot2x^{n-2}y^n+x^2y^3\cdot3x^ny^{n-3}-x^2y^3\cdot x^{n-2}y^{n-3}\)

\(=-2x^ny^{n+3}+3x^{n+2}y^n-x^ny^n\)

14 tháng 12 2018

22 tháng 12 2021

\(B=\left(x+y\right)\left(x^2-xy+y^2\right)+3xy\left[\left(x+y\right)^2-2xy\right]+6x^2y^2\left(x+y\right)\)

\(=x^2-xy+y^2+3xy\left(1-2xy\right)+6x^2y^2=x^2-xy+y^2+3xy-6x^2y^2+6x^2y^2=x^2+2xy+y^2=\left(x+y\right)^2=1\)

24 tháng 10 2021

\(a,=12x^2+18x-12x^2+x+1=19x+1\)

24 tháng 10 2021

\(a,=12x^2+18x-12x^2+x+1=19x+1\\ b,=4x^3y^4-3xy^2-\dfrac{3}{2}x\)

4 tháng 9 2021

\(a.6x^3y^2.\left(2-x\right)+9x^2y^2.\left(x-2\right)\\ =6x^3y^2.\left(2-x\right)-9x^2y^2.\left(2-x\right)\\ =3x^2y^2\left(2-x\right)\left(2x-3\right)\)

AH
Akai Haruma
Giáo viên
4 tháng 9 2021

Lời giải:

a.

$=6x^3y^2(2-x)-9x^2y^2(2-x)$

$=(2-x)(6x^3y^2-9x^2y^2)$

$=(2-x).3x^2y^2(2x-3)=3x^2y^2(2-x)(2x-3)$

b.

$=(x^2-y^2)-(4x-4y)=(x-y)(x+y)-4(x-y)$

$=(x-y)(x+y-4)$

c.

$81x^2-(9y^2-6yz+z^2)$

$=(9x)^2-(3y-z)^2=(9x-3y+z)(9x+3y-z)$

 

24 tháng 9 2021

\(a,=\left(x-2\right)\left(9x^2y^2-6x^3y^2\right)=3x^2y^2\left(3-2x\right)\left(x-2\right)\\ b,=5x\left(x^2-y^2\right)+20x\left(x+y\right)=5x\left(x-y\right)\left(x+y\right)+20x\left(x+y\right)\\ =5\left(x+y\right)\left(x^2-xy+4x\right)\\ c,=8x^2+2x-12x-3=2x\left(4x+1\right)-3\left(4x+1\right)=\left(2x-3\right)\left(4x+1\right)\)

10 tháng 10 2021

a) \(4\left(x+1\right)^3-x-1=4\left(x+1\right)^3-\left(x+1\right)=\left(x+1\right)\left[4\left(x+1\right)^2-1\right]=\left(x+1\right)\left[2\left(x+1\right)-1\right]\left[2\left(x+1\right)+1\right]=\left(x+1\right)\left(2x+1\right)\left(2x+3\right)\)

b) \(5x\left(x-3\right)+\left(3-x\right)^2-\left(x-3\right)=5x\left(x-3\right)+\left(x-3\right)^2-\left(x-3\right)=\left(x-3\right)\left(5x+x-3-1\right)=\left(x-3\right)\left(6x-4\right)=2\left(x-3\right)\left(3x-2\right)\)

c) \(9x^2y^3-3x^4y^2-6x^3y^2+16xy^4=xy^2\left(9xy-3x^3-6x^2+16y^2\right)\)